2018
DOI: 10.1097/aap.0000000000000831
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pain Is Associated With Chronic Opioid Use After Total Knee Arthroplasty

Abstract: Acute pain predicts chronic opioid use. Prospective studies of efforts to reduce acute pain, in terms of long-term effects, are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Furthermore, opioid consumption was greater in patients with higher CCI score, epilepsy, obesity (BMI >35 kg/m 2 ), knee vs hip surgery, unilateral knee replacement vs bilateral operation, TKA vs UKA, and those who used analgesics preoperatively. Previously, increased opioid consumption after hip and knee replacement has been associated with TKA vs THA, preoperative opioid or other analgesic use, psychiatric disorders (especially depression/anxiety), tobacco use, cardiac disease, younger age, greater affected joint pain, other pain sites, TKA vs UKA, use of walking aids, and female gender (9,11,13,(15)(16)(17)(18)20,21,26). In addition, obesity and the number of comorbidities (based on CCI score) have been associated with increased opioid use after knee replacement (11,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, opioid consumption was greater in patients with higher CCI score, epilepsy, obesity (BMI >35 kg/m 2 ), knee vs hip surgery, unilateral knee replacement vs bilateral operation, TKA vs UKA, and those who used analgesics preoperatively. Previously, increased opioid consumption after hip and knee replacement has been associated with TKA vs THA, preoperative opioid or other analgesic use, psychiatric disorders (especially depression/anxiety), tobacco use, cardiac disease, younger age, greater affected joint pain, other pain sites, TKA vs UKA, use of walking aids, and female gender (9,11,13,(15)(16)(17)(18)20,21,26). In addition, obesity and the number of comorbidities (based on CCI score) have been associated with increased opioid use after knee replacement (11,17).…”
Section: Discussionmentioning
confidence: 99%
“…Persistent pain may also lead to the increased consumption of analgesics (8). To date, however, only a limited number of large-scale studies have been conducted on the trajectories of analgesic consumption and the risk factors associated with increased analgesic consumption after surgery (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21), even though the risks for adverse events of opioids and non-steroidal anti-inflammatory drugs increase in long-term use (22)(23)(24), especially in elderly patients with comorbidities. Motivated by the ongoing opioid prescription crisis (25), most recent studies have focused on opioid use after joint replacement and reported higher odds for prolonged postoperative opioid use in association with psychiatric disorders, preoperative opioid use, worse preoperative pain, younger age, cardiac disease, and undergoing knee (compared to hip) surgery (9,10,(14)(15)(16)(17)(18)(19)(20)26).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent pain may also lead to the increased consumption of analgesics [8]. To date, however, only a limited number of large-scale studies have been conducted on the trajectories of analgesic consumption and the risk factors associated with increased analgesic consumption after surgery [9][10][11][12][13][14][15][16][17][18][19][20][21], even though the risks for adverse events of opioids and non-steroidal anti-inflammatory drugs increase in long-term use [22][23][24], especially in elderly patients with comorbidities. Motivated by the ongoing opioid prescription crisis [25], most recent studies have focused on opioid use after joint replacement and reported higher odds for prolonged postoperative opioid use in association with psychiatric disorders, preoperative opioid use, worse preoperative pain, younger age, cardiac disease, and undergoing knee (compared to hip) surgery [9][10][11][12][13][14][15][16][17]26].…”
Section: Introductionmentioning
confidence: 99%
“…By reducing dependence on opioids, regional techniques are presumed to affect the long-term development of hyperalgesia associated with opioids 25. Though most studies of regional techniques and multimodal analgesia do not necessarily investigate long-term outcomes of chronic pain and persistent opioid use, studies have demonstrated the association between acute pain and chronic opioid use 26. Therefore, measures taken to reduce acute pain may actually carry the potential benefit of mitigating formation of chronic pain and an ongoing dependence on opioids.…”
Section: Discussionmentioning
confidence: 99%